2015
DOI: 10.1039/c4em00564c
|View full text |Cite
|
Sign up to set email alerts
|

Formation of disinfection byproducts in a recirculating mariculture system: emerging concerns

Abstract: Disinfection is commonly employed in recirculating mariculture systems (RMS) to control animal diseases and improve seawater quality; however, little is known about the occurrence of disinfection byproducts (DBPs) formed in such RMS. Beijing Aquarium is a typical RMS with artificially prepared seawater and mainly adopts a decentralized treatment strategy for different animal tanks, including sand filtration, foam fractionation, and disinfection (O 3 , UV, and O 3 /ClO 2 ). This study reveals that the adopted d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 38 publications
(48 reference statements)
0
5
0
Order By: Relevance
“…Currently, studies on the formation of Br-DBPs have mainly focused on the disinfection of drinking water and swimming pools, and very few studies have examined the disinfection of aquaculture seawater . However, the generation of Br-DBPs during aquaculture seawater disinfection should not be underestimated because of the extremely high concentration of bromide (67 mg L –1 ) in aquaculture seawater relative to that in freshwater sources (<2 mg/L). , Recent studies on seawater disinfection have shown that considerable amounts of Br-DBPs were generated in chlorinated seawater, , most of which contained aromatic structures . More importantly, DBPs containing aromatic structures, which are more lipophilic with higher log P values (2.40–5.01) than aliphatic halogenated DBPs (0.43–1.79), more efficiently permeate cells and accumulate in marine organisms. , For instance, high levels of polybrominated diphenyl ethers and brominated phenols were found in the blood of fish and wildlife from the Baltic Sea , and in seafood, and these compounds were also determined to accumulate in dogs and cats through the ingestion of pet food .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Currently, studies on the formation of Br-DBPs have mainly focused on the disinfection of drinking water and swimming pools, and very few studies have examined the disinfection of aquaculture seawater . However, the generation of Br-DBPs during aquaculture seawater disinfection should not be underestimated because of the extremely high concentration of bromide (67 mg L –1 ) in aquaculture seawater relative to that in freshwater sources (<2 mg/L). , Recent studies on seawater disinfection have shown that considerable amounts of Br-DBPs were generated in chlorinated seawater, , most of which contained aromatic structures . More importantly, DBPs containing aromatic structures, which are more lipophilic with higher log P values (2.40–5.01) than aliphatic halogenated DBPs (0.43–1.79), more efficiently permeate cells and accumulate in marine organisms. , For instance, high levels of polybrominated diphenyl ethers and brominated phenols were found in the blood of fish and wildlife from the Baltic Sea , and in seafood, and these compounds were also determined to accumulate in dogs and cats through the ingestion of pet food .…”
Section: Introductionmentioning
confidence: 99%
“…1,5,17 Currently, studies on the formation of Br-DBPs have mainly focused on the disinfection of drinking water and swimming pools, and very few studies have examined the disinfection of aquaculture seawater. 18 However, the generation of Br-DBPs during aquaculture seawater disinfection should not be underestimated because of the extremely high concentration of bromide (67 mg L −1 ) in aquaculture seawater relative to that in freshwater sources (<2 mg/L). 4,5 Recent studies on seawater disinfection have shown that considerable amounts of Br-DBPs were generated in chlorinated seawater, 18,19 most of which contained aromatic structures.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…ClO 2 has been recently adopted as a disinfectant in some RMSs; however, its use is typically accompanied by the continuous accumulation of ClO 3 − . For example, the ClO 3 − concentration in Beijing Aquarium from our previous research could reach as high as 55 mg/L (Qiang et al, 2015), which exceeds the United States Environmental Protection Agency (USEPA)-regulated maximum contaminant level (MCL) for drinking water by a factor of nearly 55. Cl 2 is the most frequently used disinfecting agent in drinking water treatment because of its low cost and high disinfection capacity, whereas undesirable DBPs with potentially harmful health effects, especially trihalomethanes (THMs) and haloacetic acids (HAAs), can be produced in the chlorination process (Cowman and Singer, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Chemical disinfectants are widely used in such facilities to inactivate pathogens while protecting marine animal health (Wang et al, 2014), including ozone (O 3 ), chlorine dioxide (ClO 2 ), chlorine (Cl 2 ), and chloramine (NH 2 Cl). However, these disinfectants can react with water constituents, such as dissolved organic matter (DOM), ammonia, bromide (Br − ), and iodide (I − ), to form a variety of hazardous disinfection byproducts (DBPs), especially in a recirculating mariculture system (RMS) (Shi et al, 2013;Qiang et al, 2015). RMS enables the treatment of polluted water within a closed loop, offers improved control of effluent discharge, and allows complete environmental control, and thus has been preferentially employed to deal with the ecological problems associated with seawater in marine aquaculture (Sharrer et al, 2007).…”
Section: Introductionmentioning
confidence: 99%